Perceptions on the Role of Anatomy in Clinical Practice: A Questionnaire-Based Study of Medical and Dental Students - Moamer Altife Almahde; Karima Alfitory Ahmed (African Journal of Advanced Pure and Applied Sciences, 2025)
Background: Anatomical knowledge serves as a cornerstone of medical and dental education, underpinning accurate diagnosis and safe clinical practice. However, the extent to which students perceive its relevance and integration into clinical training remains a topic of ongoing discussion. Objective: To assess the perceptions of medical and dental students regarding the importance of anatomy in clinical practice and to compare responses across disciplines. Methods: A cross-sectional questionnaire-based survey was conducted among 364 students from various universities across Libya, including both pre-clinical and clinical years. The questionnaire assessed agreement levels on key statements related to the role of anatomy in clinical diagnosis, skill development, curriculum emphasis, and integration into practice. Data were analyzed using descriptive statistics and Chi-square tests to assess discipline-based differences. Results: The majority of students agreed that anatomy is essential for clinical diagnosis (87.9%) and improves clinical skills (85.2%). A significant proportion (92.0%) supported greater curricular emphasis on anatomy. However, 27.5% of respondents found it difficult to integrate anatomy into clinical practice. Comparison by discipline revealed that medical students were significantly more likely to support increased emphasis on anatomy in the curriculum compared to dental students (95.0% vs. 88.4%, p = 0.045). Conclusion: Students widely acknowledge the critical role of anatomy in clinical education. However, challenges persist in translating anatomical knowledge into practice. The findings highlight the need for curriculum reforms that promote clinically integrated anatomy teaching, tailored to the specific demands of each discipline.